Fentanyl for Epidural Intravascular Test Dose in Obstetrics. Issue 5 (September 1993) - Yoshii, Wade Y.; Kotelko, Dennis M.; Rasmus, Kathleen T.; Miller, Megan; Wright, William C.; Rosen, Peter J.; Rottman, Richard L.; Stone, Joseph J.
Abstract : Background and Objectives: Although dizziness and drowsiness may be produced with either intravenous or epidural fentanyl, their occurrence after an intravenous injection is more rapid and relatively more pronounced. The purpose of this study was to determine whether or not the difference between routes of administration would be a reliable method of detecting an accidental intravascular injection. Methods: In part 1, using a double-blinded protocol, we prospectively assessed in laboring women the incidence of dizziness, drowsiness, or both associated with intravenous fentanyl (100 μg). In random order, subjects received two peripheral intravenous injections: 2 ml of fentanyl and 2 ml of saline, separated by a 3-minute observation period. Results: In group 1 (18/18) and group 2 (22/22), all subjects reported a response to intravenous fentanyl within the one-minute assessment. In part 2, we evaluated in laboring patients the frequency of dizziness, drowsiness, or both to epidural fentanyl (100 μg). The study design was identical to part 1; however, the subjects received 2 ml of fentanyl and 2 ml of saline via a functional epidural catheter. In group 3 (1/18) and group 4 (1/22), one subject reported a response to epidural fentanyl within the 3-minute observation period. Conclusions: Overall, the responses to intravenous fentanyl (40/40) occurred in a remarkably more consistent fashion when compared to epidural fentanyl (2/40). Thus, the results suggest that in laboring patients, intravenous fentanyl produces predictable and easily detectable changes that may be useful in identifying an epidural catheter unintentionally placed intravascularly.